Development of a computer application to calculate cyclists front area in studies about aerodynamics - Pivetta Carpes, F.; Rossato, M.; Dias da Silva, A.; Bolli Mota, C. (ISB Congress, 2005)
The aim of this study was to propose a method to calculate the cyclist front area through tools of images processing, with the development of a computer application, searching to provide results that can be used in the analysis of aerodynamics in cycling.